2020
DOI: 10.1177/2514848620920743
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the green panopticon: New directions in research exploring environmental governmentality

Abstract: This introduction to the special collection explores how a revised or expanded understanding of ‘environmentality’ can further our analysis of the evermore complex terrain of environmental politics today. We offer an outline of the literature from which the discussion emerges and how the subsequent articles both engage with and depart from it. We describe the origin of the ‘green governmentality’ discussion following the rise of global sustainable development discourse. We then explain how this initial explora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 43 publications
0
13
0
1
Order By: Relevance
“…This multiple environmentality perspective has been productively employed by a growing body of researchers to explore intricacies of environmental policies and behaviours in a variety of contexts (see e.g. Youdelis 2013;Fletcher 2017;Montes 2020;Fletcher and Cortes-Vazquez 2020).…”
Section: Environmentality Novel Modalities and Tekmentioning
confidence: 99%
“…This multiple environmentality perspective has been productively employed by a growing body of researchers to explore intricacies of environmental policies and behaviours in a variety of contexts (see e.g. Youdelis 2013;Fletcher 2017;Montes 2020;Fletcher and Cortes-Vazquez 2020).…”
Section: Environmentality Novel Modalities and Tekmentioning
confidence: 99%
“…Studies of modern government through the lens of governmentality have revealed that governance as a manifestation of power takes place in multiple sites, through different discourses, and often outside the traditional boundaries of the state (Dean 2009, Allen 2004Murdoch 2006;Rutherford 2007;Ettlinger 2011). A growing body of literature attends to the concept of "green governmentality" and multiple governmentalities in environmental governance (see Fletcher and Cortes-Vazquez 2020) but the Blue Economy is yet to feature. There have, however, been a few studies of the BE as discourse (as noted earlier), discourse being an important element of the operationalisation of governmentalities.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Much critical discussion in environmental governance currently falls under the rubric of 'environmentality'-building on Foucault's original concept of 'governmentality'-referring to the subtle ways that environmental behaviour is regulated through the development of new subjectivities, or new environmental values and moralities (Agrawal, 2005). There are a variety of environmentalities (Fletcher, 2017;Asiyanbi, Ogar and Akintoye, 2019;Fletcher and Cortes-Vazquez, 2020), including the ways that local communities resist or adapt to new forms of environmental governance (Morrison et al, 2019). For instance, empirical work has critiqued the market-based focus of many climate tools and conceptual frameworks, such as REDD+, ecological modernization and carbon trading and offsetting (Knox-Hayes, 2015;Watt, 2018;Song et al, 2021), resonating with literature that explicitly critiques their morality (Caney, 2010).…”
Section: Power Dynamics Of Multiple Moralitiesmentioning
confidence: 99%
“…This emphasis on multiple rationalities has highlighted the interactions between environmental and climate governance strategies and the subjects of those strategies (e.g. McGregor et al, 2015;Malier, 2019), and has helped to investigate and interpret the gaps between the visions of climate decision-makers and the implementation of decisions on the ground (Collins, 2020;Fletcher and Cortes-Vazquez, 2020). In their discussion of REDD+ in Nigeria, for example, Asiyanbi et al, (2019) describe how it aimed to normalise particular moral values about forest protection but were countered by local discourses of morality centred around entitlements to forests.…”
Section: Power Dynamics Of Multiple Moralitiesmentioning
confidence: 99%